The interaction between sulfathiazole and cobalt(II): potentiometric studies - Bellú, Sebastián (2007)
Potentiometric studies of sulfathiazole (HST) in the presence and absence of cobalt(II) were performed. Equilibrium constants for the formation of the detected species, [Co(ST)]+ and [Co(ST)(OH)], are reported. UV-Vis spectrophotometric measurements suggest that the coordination Co(II)-sulfathiazole might be through a N atom, which, in agreement with MO calculations, could be a thiazolic one. In spite of sulfonamides being better ligands at pH >7, [Co(ST)]+ was found at pH ≈ 3.